Minimally Invasive Approach for Cardiac Hemangioma Resection in a Teenager. Issue 4 (July 2022) - Thornton, Steven W.; Hoover, Anna C.; Nellis, Joseph R.; Overbey, Douglas M.; Andersen, Nicholas D.; Haney, John C.; Turek, Joseph W.
Cardiac hemangiomas are a rare tumor traditionally resected by median sternotomy. We performed a minimally invasive right ventricular cardiac hemangioma resection via a left anterior mini-incision (LAMI). The procedure was without complication, and the patient was discharged on postoperative day 2. The LAMI has been used broadly by our team for operations involving the right ventricular outflow tract, as an alternative to median sternotomy. Here we show that it can also be used for the resection of a cardiac tumor.